The "lessons" of the Australian "heroin shortage" - Gilmour Stuart; Day Carolyn; Degenhardt Louisa; Hall Wayne (BMC, 2006)
Abstract Heroin use causes considerable harm to individual users including dependence, fatal and nonfatal overdose, mental health problems, and blood borne virus transmission. It also adversely affects the community through drug dealing, property crime and reduced public amenity. During the mid to late 1990s in Australia the prevalence of heroin use increased as reflected in steeply rising overdose deaths. In January 2001, there were reports of an unpredicted and unprecedented reduction in heroin supply with an abrupt onset in all Australian jurisdictions. The shortage was most marked in New South Wales, the State with the largest heroin market, which saw increases in price, dramatic decreases in purity at the street level, and reductions in the ease with which injecting drug users reported being able to obtain the drug. The abrupt onset of the shortage and a subsequent dramatic reduction in overdose deaths prompted national debate about the causes of the shortage and later international debate about the policy significance of what has come to be called the "Australian heroin shortage". In this paper we summarise insights from four years' research into the causes, consequences and policy implications of the "heroin shortage".